Preparing carbon black aerogel quickly by chemical vapor deposition. (January 2023) - Zhou, Xunpeng; Wang, Yafeng; Xiao, Lijun; Zhang, Mingyu; Su, Zhean; Huang, Qizhong
Abstract: Carbon black aerogel, a new type of carbon aerogel made of carbon black, has been prepared rapidly and inexpensively by chemical vapor deposition without catalyst. In just 5 h, more than 0.8 kg of carbon black aerogel were obtained from a mixture of propane and argon. With a well-developed branching network structure and good graphitization, carbon black aerogel has a low density (0.11 g/cm 3 ), high compressive strength (0.543 MPa), extremely low thermal conductivity (0.049 W/(m·K)) and outstanding super-hydrophobic properties. A discussion also is given about the process of forming aerogels using carbon black as the base material. This finding may explore a cost-effective method of fabricating carbon aerogels and enrich the variety of carbon materials available. Graphical abstract: Image 1 Highlights: Carbon black aerogel, a new type of carbon aerogel, has been prepared by chemical vapor deposition. Carbon black aerogel is manufactured in large quantities and low-cost in a short time without catalyst. Using carbon black particle as a base material to form carbon aerogel. Carbon black aerogel has characteristics such as low density, low thermal conductivity, good electrical conductivity, super-hydrophobic and so on. Revealed the process of carbon black transform to aerogels, make it possible to produce carbon aerogels cheaply and efficiently.